RESPONDING TO MUHAMMADIYAH EDUCATORS IN THE AGE OF NEUROTECHNOLOGY: IMPLICATIONS FOR THE DEVELOPING OF ISLAMIC EDUCATION - Jailani, Mohammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
There is a holistic differentiation of educational alliances which has received a warm response from multicultural Islamic education. The emergence of a homogeneous educational base with all its knick-knacks, giving rise to new cases or chapters in Islamic education. Haedar Nashir responded well to this in his scientific speech, as delivered on the 48th Mukhtamar Muhammadiyah day at UMS Surakarta, the content of his scientific speech was none other than the advancement of Muhammadiyah Islamic education in the Millennial era. This research responds to the polemic of Islamic education in Indonesia along with alternative approaches based on Islam in the current era. Estuary based on qualitative descriptive research about the rumors of Islamic education in Indonesia. This research is based on a qualitative approach to literature review. Data analysis was used with a content analysis approach. Notes The results of the study found that polemics about life and about learning, approaches, methods, information delivery, education management, and social media appear, in the present. The level of demands from the Ministry of Education and Culture and the Ministry of Religion that Islamic education is expected to be able to bring more enlightenment. But what is the power of Islamic education in Indonesia, it is still as usual, progressing not advancing and not retreating. Differentiation of educational alliances occurs everywhere, regardless of formal education or Islamic boarding school education. Researchers offer alternatives in the increasingly significant decline in education with several alternative approaches such as neuroscience-based learning, religious moderation-based learning, and knowledge management in Islamic education. The contribution and implications of this research lead to the improvement of Islamic education and learning based on Islamic studies, which in the current era are starting to be shunned by millennials and generation Z in the era of society 5.0. This research is a forum and foundation for the improvement and progress of Islamic civilization in the future.